2019
DOI: 10.24203/ajas.v7i1.5660
|View full text |Cite
|
Sign up to set email alerts
|

Food and Trophic Relationships of Four Mullet Fish (Mugilidae) in the Shatt Al-Arab River, Iraq

Abstract: Food composition and feeding relationships of four mullet species, Planliza abu, P. subviridis, P. klunzingeri and Osteomugil speigleri from the Shatt Al-Arab River, Iraq, were assessed during 2016-2017.Fish were captured by gill nets, cast net and electro-fishing. The index of relative importance (IRI%) of food item was determined by combined the frequency of occurrence and points methods. Monthly variations in feeding activity and intensity of all species were observed. All species were herbivorous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Previous studies supported the result, for instance, Wijeyaratne and Costa (1990) revealed that Liza vaigiensis was omnivorous grazers with RGL ranging from 2.31 to 3.43. Four mullet species from the Shatt Al-Arab River, Iraq, Planliza abu, P. subviridis, P. klunzingeri, and Osteomugil speigleri were herbivorous (Mohamed & Abood, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies supported the result, for instance, Wijeyaratne and Costa (1990) revealed that Liza vaigiensis was omnivorous grazers with RGL ranging from 2.31 to 3.43. Four mullet species from the Shatt Al-Arab River, Iraq, Planliza abu, P. subviridis, P. klunzingeri, and Osteomugil speigleri were herbivorous (Mohamed & Abood, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies supported the result, for instance, Wijeyaratne and Costa (1990) revealed that Liza vaigiensis was omnivorous grazers with RGL ranging from 2.31 to 3.43. Four mullet species from the Shatt Al‐Arab River, Iraq, Planliza abu , P. subviridis , P. klunzingeri , and Osteomugil speigleri were herbivorous (Mohamed & Abood, 2019). The feeding habit exhibited great variability depending on species, habitat, season, and even within the same species due to the spatiotemporal change of food composition (Islam et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However Lazem (2009) considered it a detritivore in Garmat Ali channel because of the presence of organic and non-organic detritus in their food while their food include diatoms, algae, aquatic plants and protozoa as well as sand and clay granules in the east of Al-Hammar marshes (Mutlak, 2012). Diatoms were the dominant item in the gut of Abu mullet during the study of Mohamed & Abood (2019).…”
Section: Discussionmentioning
confidence: 99%
“…Food resources are one of the important factors for fish that can determine the extent of distribution and control of fish populations (Khoncara et al 2018). The majority of mullets are known as detritivorous fish because their food is available in the form of organic matter manifested in the bottom sediments (Mohamed and Abood 2019). Mullets may also consume macroalgae, plankton, microorganisms, and other organic substances, including fine and coarse particle organic matter (Garcia et al 2018).…”
Section: Population and Ecological Aspect Of Ichthyofauna In Pematang...mentioning
confidence: 99%